Investigation of post-operative pain levels and nursing ınterventions following gynecologic surgery - Selda Rizalar; Nazlı Baltacı; Şengül Kahraman (Tehran University of Medical Sciences, 2015)
Background & Aim: Nowadays, new methods related to pain management have emerged. However, it has been reported in studies that post-operative pain management is inadequate. The purpose of this study was determined to pain levels of the patients after gynecologic surgery and nursing interventions. Methods & Materials: This descriptive study was undertaken as a multicenter study in the gynecologic surgical departments of the university and state hospital in Samsun. 221 patients who had an operation in first 48 hours post-operative, were participated in the study voluntarily, were included in the study sample. Data were collected by questionnaire and visual analog scale (VAS). Data were evaluated with percentage, mean, Mann-Whitney U and Kruskal-Wallis tests. Results: It was determined that the patients were experienced severe pain according to VAS (7.23 ± 2.79). It was found a significant relationship between the pain scores and marital status, smoking habit, and operation length of the patients. It was found that the most common applied nursing pain management intervention were preparing a comfortable and quiet environment and giving information about effects of the disease and drugs. It was found that nurses were not used imagination and music. Conclusion: This study was showed that the patients were experienced severe pain the early period after gynecologic surgeryand that frequency of non-pharmacologic methods of nurses were veryfew in pain management.